THE INFLUENCE OF WORD OF MOUTH AND SOCIAL MEDIA MARKETING ON CUSTOMER PURCHASE INTENTION AT MSMES COFEE SHOPS IN MANADO - Lontoh, Patricia D. V. P.; Tumbuan, Willem J. F. A.; Wangke, Shinta. J. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
At this time there is a lot of businesses like Micro, Small, and Medium Enterprises or usually known by MSMEs, having a shortage of income and also reducing the numbers of costumer, it is because of COVID-19 pandemic. All the coffee shops MSMEs, are racing to stay being in existed. They are using the technique of marketing that having goals to pull the interest of customers for buying up. Because of that, writer wanted to know the consequence and the technique of marketing, in the perspective of the customers. Writer assumed, that there are two marketing technique like, Word of Mouth (WOM) and Social Media Marketing that could make customers having intention to purchase. Research has been done by the writer using the Quantitative Method, by spreading the Questionnaire to 100 people in respondent at Manado. Let there be the result from this result can gives us positive impact, more then it will help the continuity of MSMEs Coffee Shops in Manado.Â Â Keywords: word of mouth, social media marketing, purchase intention, quantitative